A meta-analysis: retrograde intrarenal surgery vs. percutaneous nephrolithotomy in children - Yuan, Yi; Liang, Yan-nei; Li, Kai-feng; Ho, Yi-ru; Wu, Qian-long; Zhao, Zhang (Frontiers in Pediatrics, 2023)
Backgrounds The increasing prevalence of pediatric kidney stones worldwide makes minimally invasive lithoclasty like retrograde intrarenal surgery(RIRS) and percutaneous Nephrolithotomy (PCNL) more prevalent. However, their safety and efficacy are controversial. Consequently, a meta-analysis of the comparison between RIRS and PCNL is conducted. Methods Clinical trials were selected from PubMed, EMBASE, Scopus, and Cochrane Library databases. The data extraction and study quality assessment were performed by two individuals independently. The data relating to therapeutic effects were extracted and analyzed by Review manager 5.4. Backgrounds The increasing prevalence of pediatric kidney stones worldwide makes minimally invasive lithotripsy like retrograde intrarenal surgery (RIRS) and percutaneous Nephrolithotomy (PCNL) more prevalent. However, their safety and efficacy are controversial. Consequently, a meta-analysis of the comparison between RIRS and PCNL is conducted. Methods Clinical trials were selected from PubMed, EMBASE, Scopus, and Cochrane Library databases. The data extraction and study quality assessment were performed by two individuals independently. The data relating to therapeutic effects were extracted and analyzed by Review manager 5.4. Results Thirteen studies involving 1019 patients were included. The micro-PCNL excelled in stone-free rate (P=0.003), postoperative fever rate (P=0.02), and Clavien-Dindo II complications (P=0.05). Notably, the mean age of the micro-PCNL group was younger than other groups (P=0.0005). The operation time in mini-PCNL was longer than RIRS (p<0.00001) but with high heterogeneity (I^2=99%). There was no difference in Clavien-Dindo I, II, and III complications between the PCNL and the RIRS, but mini-PCNL showed a higher probability than RIRS in Clavien-Dindo I (P=0.0008) and II complications(P=0.007). Conclusions Compared with RIRS, micro-PCNL could be a better therapeutic option for kidney stones in children. Of note, more parameters should be analyzed to illustrate the efficacy of different minimally invasive surgeries for pediatric kidney stones due to poor cases in our study.